Aplikasi Lean Six Sigma sebagai Upaya Pengurangan Defect Produk Water Pump - Anni Intan Faricha; Yugowati Praharsi; Farizi Rachman (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
The foundry company has a commitment to always prioritise product quality, the exact dimensions of the products resulting from the finishing CNC process, are classified as without defects. Water Pump products are targeted that have a high reject rate, due to defects in the form of CNC dimension failure, bad casting and 5 variance of te defects. The results of processing Non Conformance Report waster pump products, the number of product quantity increases in production, this successfully proves that there is a defect waste process behaviour. This research applies Six Sigma method for reduce defect. This method includes DMAIC, Define critical waste defect (SIPOC), Measure with DPMO and sigma value Analyze with Fishbone Diagram, Improve with Kaizen resulting in an output sigma level value of 2.98 which rose to 3.00 with a DPMO value from 69,178 to 67,702 due to improvements as well as a predetermined target increase in the sigma level value.